OVERVIEW OF SATISFACTION SOCIETY OF SERVICE COUNTER REGISTRATION OF OUTPATIENT HEALTH - Azizah, Andi; Bujawati, Emmi; Arranury, Zil Fadhilah (Homes Journal: Hospital Management Studies Journal, 2022)
Background:At this time the basic need of the Indonesian people to be able to live a decent and productive life is health, with this it is necessary to provide health services that are in line with the aim of accessing quality health services. The role of the puskesmas as the first level of health care provider needs to maintain the quality of service so that patients feel satisfied. objectives: This study aims to describe the community’s satisfaction with the outpatient registration service at the Baraka Health Center, Baraka District, Enrekang Regency. Method: This type of research is a quantitative research using a cross sectional study design. The population in this study were all people who were in the working area of the Baraka Community Health Center. Result : The results showed that the satisfaction level of respondents at the Baraka Health Center was mostly satisfied with the service at the outpatient registration counter. Conclusion : The researcher recommends the health workers of the Baraka Health Center, especially the registration counter service, to give a better impression to the people who come for treatment.